2020
DOI: 10.1016/j.msea.2020.139691
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and strengthening mechanism of ultrasonically soldered 7075 Al joint using Ni-foam/Sn composite solder foil

Abstract: Ni-foam reinforced Sn-based composite solder was employed to join ultrafine grain 7075 Al alloy with the assistance of ultrasound. The solder seam was mainly composed of Ni skeletons, Sn-based solder, α-Al phase and very fine (hundreds of nanometers to several microns diameter) Ni3Sn4 particles. Discontinuous networks surrounded by the fine Ni3Sn4 and α-Al particles were in-situ formed in the solder seam, the diameter of which was decreased with increasing soldering time. Smooth transition of the lattice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Our current research included fabricating and using Ni foam reinforced Sn composite solder foils to solder Cu alloy and Al alloy, and it revealed that the use of Ni-skeletons and Ni-Sn reactants significantly increased the strengths of joint [6] , [7] . The analysis results show that continuous reticular structure inhibits the aggregation of the reinforcing phase and improves the combination between Sn solder and reinforcing phases [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Our current research included fabricating and using Ni foam reinforced Sn composite solder foils to solder Cu alloy and Al alloy, and it revealed that the use of Ni-skeletons and Ni-Sn reactants significantly increased the strengths of joint [6] , [7] . The analysis results show that continuous reticular structure inhibits the aggregation of the reinforcing phase and improves the combination between Sn solder and reinforcing phases [8] .…”
Section: Introductionmentioning
confidence: 99%